Good corporate governance practices and voluntary disclosure in companies listed in the Indonesia Sharia Stock Index (ISSI) - Avininda Dewi Nindiasari (Faculty of Business & Economics, Universitas Islam Indonesia, 2021)
Objectives: This study aims to determine the effect of the size of the board of commissioners, the proportion of independent commissioners, family ownership, and audit quality on the level of voluntary disclosure of the company.Design/methodology/approach: An empirical study of 50 companies listed in the Indonesia Sharia Stock Index (ISSI) is conducted using the 2015-2016 annual report. The type of data used is secondary data. The analytical method used in this study is multiple linear regression analysis with SPSS 21.Findings: The results of statistical tests indicate that the size of the board of commissioners and audit quality have a positive and significant effect on the level of voluntary disclosure, while the proportion of independent commissioners and family ownership has no significant effect on the level of voluntary disclosure.Implications: The main implications of the results of this study are the size of the board of commissioners and the audit quality. The size of the board of commissioners has a strong relationship to the level of voluntary disclosure. There is a relationship between the number of the board of commissioners and the national laws that have an impact on monitoring the transparency process and the effectiveness of communication within the company. For audit quality, companies that use Big Four audit firms have an effect on the level of voluntary disclosure since their financial reporting will result in better audit quality with a high level of independence. The results of this study also support that agency theory is able to partially explain the phenomenon of the relationship between corporate governance practices and the level of voluntary disclosure in companies listed in ISSI.Originality/Value: This research is one of the studies that draw a relationship between the size of the board of commissioners and audit quality on the level of voluntary disclosure of companies in Indonesia. This finding provides confidence that the size of the board of commissioners and audit quality complement each other to improve the quality of voluntary disclosure.